Theoretical aspects of linking consumer innovativeness to performance indicators - Kecskés, Zsuzsanna (Marketing & Menedzsment, 2019)
Marketing and innovativeness was connected first in 1962, when Rogers proved innovative customer’s positive impact on new product’s take-up. Since then innovativeness is still on the marketing researcher’s agenda, driven by saturated markets and growing need for further segmentation in most industries. This article aims to provide a practical approach to customer innovativeness. It is presented through exhaustive literature review how differently innovativeness has been conceptualized by the academics of management sciences. Furthermore, as its main contribution, this article attempts to establish the theoretical background to link the „soft” category of innovativeness to „hard” performance indicators like market share, sales growth, customer equity and customer lifelong value.